IMPLEMENTASI KEBIJAKAN KESEHATAN GRATIS UNIVERSAL COVERAGE DI KOTA MANADO (Suatu Studi Di Dinas Kesehatan Kota Manado) - RUMAGIT, MICHAEL (Sam Ratulangi University, 2014)
Health becomes a very important factor in running a person's activity and to supportthe community's economy Manado city. Therefore, the government launched a program Manado FreeUniversal Health Coverage in order that the whole community of Manado in health guarantee. Thepurpose of this study was to determine how the free Health Policy Implementation Universal Coverage.This study used qualitative methods. Research of respondents are not quantified, according to theneeds of research. Technique data collecting use interview guide. The data analysis technique used isdescriptive qualitative.The results analysis showed: (1) reduction found that the program has good staying UniversalCoverage attention again things unfinished (2) Presentation found there are still things that need to beconsidered is a hospital employee benefits. Based on the results of the statistical analysis concludes thatfree Health Policy Implementation Universal Coverage positive influence on the community and the cityof Manado.Based on the conclusion of the study suggested: (1) In terms of all the important aspects of thisprogram, the government should be more attention to the state of the people who need governmentguarantees are still complaining especially difficult due to the care of the program (2) In terms ofresources available funds, more attention again to employee benefits and nurses there so that all partiescan be pleased with this program.Keywords: Free Health, Universal CoveragePENDAHULUANImplementasi Kebijakan kesehatangratis Universal